Identification of a Cuproptosis-Related Molecular Signature for Predicting Biochemical Recurrence in Prostate Cancer - Chen, Dong-Ning; Wu, Xiao-Hui; You, Qi; Zhuang, Rui-Bin; Ruan, Zhong-Tian; Zhu, Jun-Ming; Zheng, Qing-Shui; Chen, Ye-Hui; Wei, Yong; Lin, Xiao-Dan; Xue, Xue-Yi (Combinatorial Chemistry & High Throughput Screening, 2026)
<span class=
Keywords: biochemical recurrence